Input and Output marketing Systens: A Nigerian Case - Olayide, S. O.; Idachaba, Francis Sulemanu (International Food Policy Research Institute, 1987)
Nigeria and many other sub-Saharan countries are rinding that adoption of new high-yielding varieties is severely constrained by existing farm input supply and food-marketing systems. Like other sub-Saharan countries, Nigeria imports most of her modern inputs because of the nearly complete absence of domestic manufacturing capabilities. Availability of these inputs to farmers depends on procurement and internal distribution efficiency. Unlike many other African countries, Nigeria in recent times has not had to depend on price taxation of crops to secure revenue. Yet output-marketing systems continue to put severe constraints on output growth.